I thought my soul would rise and fly : the diary of Patsy, a freed girl - Hansen, Joyce (New York : Scholastic Inc, 1997)
12 years old Patsy keeps a diary of the ripe but confusing time following the end of the Civil War and the granting of freedom to former slaves.